Win or lose the battle for creativity: The power and perils of intergroup competition - BAER, Markus (Institutional Knowledge at Singapore Management University, 2010)
Integrating and refining social interdependence theory and structural adaptation theory, we examined the effects of intergroup competition on the creativity of 70 four-person groups engaged in two idea generation tasks. We manipulated both group membership change (change, no change) and intergroup competition level (low, intermediate, high). Competition had the expected U-shaped relation with creativity in open (membership change) groups but failed to produce the hypothesized inverted U-shaped pattern in closed (no membership change) groups. In the latter, effects were positive for low to intermediate competition and flat for intermediate to high levels. Within-group collaboration mediated these effects.